Efficacy of medicinal plants in subduing of yellow mosaic disease in urdbean (Vigna mungo L.). (2nd October 2021) - Saeed, Sabiha; Ashraf, Shabbir; Akram, Mohammad
Abstract: Eco-friendly approach has aimed to suppress the yellow mosaic disease in urdbean. For that extracts of medicinal plants were used as spray on plants at 20 and 45 days after sowing. All treatments were effective in decreasing disease and whitefly count and enhanced yield and plant growth parameters. Application of 20% Datura stramonium extract was highly effective in reducing disease incidence, severity and whitefly resulted enhanced yield 710.41 kg/hectare during first year and 637.83 kg/hectare during second year as compared to control 410.91 kg/hectare and 365.66 kg/hectare, respectively. Data recorded during both consecutive year revealed that all the treatments are helpful in increasing number of pods, root nodules and total chlorophyll content of plant as compared to control. It is concluded that spraying of 20% leaf extract of D. stramonium is recommended to manage YMD and also to improve the overall yield of the crop.